2012
DOI: 10.1063/1.4769736
|View full text |Cite
|
Sign up to set email alerts
|

Band bending and determination of band offsets in amorphous/crystalline silicon heterostructures from planar conductance measurements

Abstract: An analytical model for the calculation of the band bending in amorphous/crystalline silicon (a-Si:H/c-Si) heterojunctions is presented and validated by comparison with full numerical simulations. The influence of the various structure properties and parameters, such as the density of states in bulk a-Si:H or at interface defects, the position of the Fermi level in a-Si:H, the temperature dependence of band gaps, is investigated. Significant band offsets imply the presence of a strong inverted layer at the c-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…However in the low temperature range one has to take care of transport in a-Si:H and to the TCO/aSi:H interface that can also have an impact on the transition temperature above which the regime fully determined by strong inversion prevails. Note that the obtained range for the conduction band offset agrees with the values determined in our group from planar conductance measurements [22] and in other groups using other techniques [23]; to pay again tribute to Cohen, we can notice that he also published early results on the a-Si:H/c-Si band offsets from capacitance measurements, however not directly on solar cells and using another experimental method and procedure (namely from a voltage filling pulse method) and he also concluded that most of the band offset between a-Si:H and c-Si occurs at the valence band [27]. The depletion layer approximation had been first criticized by Gummel and Scharfetter from calculations on p þ n step homojunctions where these authors showed that the intercept voltage in highly dissymmetric junctions is not as expected from the simple depletion approximation [28].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However in the low temperature range one has to take care of transport in a-Si:H and to the TCO/aSi:H interface that can also have an impact on the transition temperature above which the regime fully determined by strong inversion prevails. Note that the obtained range for the conduction band offset agrees with the values determined in our group from planar conductance measurements [22] and in other groups using other techniques [23]; to pay again tribute to Cohen, we can notice that he also published early results on the a-Si:H/c-Si band offsets from capacitance measurements, however not directly on solar cells and using another experimental method and procedure (namely from a voltage filling pulse method) and he also concluded that most of the band offset between a-Si:H and c-Si occurs at the valence band [27]. The depletion layer approximation had been first criticized by Gummel and Scharfetter from calculations on p þ n step homojunctions where these authors showed that the intercept voltage in highly dissymmetric junctions is not as expected from the simple depletion approximation [28].…”
Section: Discussionsupporting
confidence: 85%
“…(12), one then obtains that the valence band offset is almost zero. This is much less than values reported recently in the literature: about 0.4 eV obtained from planar conductance measurements performed on (p) a-Si:H/ (n) c-Si interfaces coming from various institutes [22] and similar values (or even larger for higher hydrogen content and thus larger band gap of a-Si:H) obtained from photoelectron spectroscopy [23]. In addition, we can note that the value of V int ¼ 0.56 V is much lower than the open circuit voltage measured under normalized AM1.5G conditions, V oc ¼ 725 mV.…”
Section: Bias Dependencementioning
confidence: 46%
“…11 We then find a simple expression for the potential drop in c-Si as a function of the total potential drop V d…”
mentioning
confidence: 99%
“…14,15 Until now, the inversion layer has been considered only as a tool to characterize the band offsets at the a-Si:H/c-Si interface 16,17 and its influence on lateral transport in operating devices has not yet been analyzed. Lateral transport through an inversion layer is successfully leveraged in modulationdoped field-effect transistors 18 and in metal-insulatorconductor inversion layer solar cells.…”
Section: Introductionmentioning
confidence: 99%